Research of the profile's geometry of screw conveyors, which are forming part of transport systems for moving carton packages - Derenivska, Anastasiia; Gavva, Oleksandr M.; Lyubimov, Valeriy (My University, 2014)
Present an analysis moving package process by means of screw conveyer packing machine with consideration of geometrical parameters package and given moving law. Purpose of the conducted research of determination of optimal geometrical and kinematics parameters screw conveyer which will enable to provide trouble-free high-performance packing automatic machine and choice recommendation of moving package law. Наведено аналіз процесу перевантаження упаковки в шнековому конвеєрі пакувальної машини. Мета проведеного дослідження визначення оптимальних геометричних та кінематичних параметрів шнека, що дасть можливість забезпечити безперебійну високопродуктивну роботу пакувальної машини-автомату.
Keywords: carton boxes; timing screw conveyors; transport system; packing machine; картонна пачка; шнековий конвеєр; транспортна система; пакувальна машина; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки